Hepatocellular Carcinoma Within the Milan Criteria: A Novel Inflammation-Based Nomogram System to Assess the Outcomes of Ablation - Chen, Shuanggang; Ma, Weimei; Cao, Fei; Shen, Lujun; Qi, Han; Xie, Lin; Wu, Ying; Fan, Weijun (Frontiers in Oncology, 2020)
Objectives Few studies based on pretreatment inflammation-based scores focused on assessing the prognosis of hepatocellular carcinoma (HCC) patients within the Milan Criteria after ablation. This study aimed to construct a nomogram based on a novel inflammation-based score for those patients. Methods A total of 635 HCC patients within the Milan Criteria after ablation meeting the inclusion and exclusion criteria were included in the study. The novel inflammation-based score─Albumin-Platelet Score (APS) was constructed by Cox proportional‑hazards modeling. The nomogram based on APS was constructed by multivariate analysis and the “rms” R package. The performance of the APS and the nomogram were assessed by time-dependent receiver operating characteristic and the concordance index (C-index). Results The APS was an integrated indicator based on peripheral albumin (ALB) level and Platelet (PLT) counts, which was significantly superior to other inflammation-based scores (NLR, PLR, PNI, mGPS, GPS, PI and CAR) in predicting the long-term prognosis of those patients undergoing ablation (P<0.05). An easy-to-use nomogram based on three pretreatment clinical variables (ie, the APS, Tumor size and Age) was constructed and further improved significantly the performance in predicting the prognosis in patients within the Milan Criteria after ablation (P<0.05). The C-index of nomogram for overall survival (OS) was 0.72 (95% CI: 0.66，0.77). The calibration plots with 1000 cycles of bootstrapping were well-matched with the idealized 45° line. Conclusions The APS was a better inflammation-based prognostic system than others. And the nomogram based on the APS improved the performance of predicting the prognosis of HCC patients within the Milan Criteria after ablation.